2018
DOI: 10.3389/fgene.2018.00610
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Alcohol Exposure: Profiling Developmental DNA Methylation Patterns in Central and Peripheral Tissues

Abstract: Background: Prenatal alcohol exposure (PAE) can alter the development of neurobiological systems, leading to lasting neuroendocrine, neuroimmune, and neurobehavioral deficits. Although the etiology of this reprogramming remains unknown, emerging evidence suggests DNA methylation as a potential mediator and biomarker for the effects of PAE due to its responsiveness to environmental cues and relative stability over time. Here, we utilized a rat model of PAE to examine the DNA methylation profiles of rat hypothal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 147 publications
(190 reference statements)
2
26
0
Order By: Relevance
“…Ethanol and ROS can modify the activity of methyltransferases and demethylases, directly affecting the global DNA methylation pattern during development. A recent study performed in mice after PAE found 118 differentially methylated regions (DMRs) related to transcription factor binding sites (223). The pathways affected by these DMRs were epigenetic remodeling, hormonal signaling, metabolism, and immune response, revealing persistent occurrence of these alterations in all developmental stages (223).…”
Section: Epigenetic Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethanol and ROS can modify the activity of methyltransferases and demethylases, directly affecting the global DNA methylation pattern during development. A recent study performed in mice after PAE found 118 differentially methylated regions (DMRs) related to transcription factor binding sites (223). The pathways affected by these DMRs were epigenetic remodeling, hormonal signaling, metabolism, and immune response, revealing persistent occurrence of these alterations in all developmental stages (223).…”
Section: Epigenetic Modificationsmentioning
confidence: 99%
“…A recent study performed in mice after PAE found 118 differentially methylated regions (DMRs) related to transcription factor binding sites (223). The pathways affected by these DMRs were epigenetic remodeling, hormonal signaling, metabolism, and immune response, revealing persistent occurrence of these alterations in all developmental stages (223). Demethylation following ethanol exposure causes a decrease in IGF-2 levels in utero, generating an important delay in growth and leading to skeletal malformations (224).…”
Section: Epigenetic Modificationsmentioning
confidence: 99%
“…Individual values are represented by square (Sham) and dots (LPS) for each gene and box plot represent minimal to maximal value with line at median many neurodevelopmental and neurodegenerative diseases including autism spectrum disorder, Down syndrome, Alzheimer disease, and schizophrenia. 62,63 It was suggested that methylation in intergenic and introns could target regulatory sequences that play a role in gene expression. In accordance to our results, animal studies showed that adverse events during the perinatal period can lead to sustained alteration of the brain methylome up to 1 year after the initial insult.…”
Section: F I G U R E 4 Methylation Levels Of Genes Of Interest Associmentioning
confidence: 99%
“…In our study, neonatal inflammation-induced WMI resulted in DNA methylation alteration that persisted up to 21 days post-injury. [63][64][65][66] One major group of pathways that emerged from our methylome analysis following neonatal inflammation-induced WMI was related to the axon. 61,62 For example, exposure to maternal maltreatment during the first days of life in rats induced a global alteration of DNA methylation in the amygdala and hippocampus at adolescence (P30).…”
Section: F I G U R E 4 Methylation Levels Of Genes Of Interest Associmentioning
confidence: 99%
“…Mouse and rat studies showed the association between prenatal ethanol exposure and gene expression changes in postnatal and adult stages [34][35][36][37] . This study examined ethanol-induced gene expression changes during embryogenesis before gastrulation.…”
Section: Discussionmentioning
confidence: 99%